Screening And Quantification Of Phytochemicals In Leaf Extracts Of Schrebera Swietenioides And Homalium Zeylanicum - VELAVARTHIPATI ANURADHA DEVI; KOKKANTI MALLIKARJUNA (International Journal of Pharma and Bio Sciences, 2015)
Phytochemical screening and quantification in leaf extracts of Schrebera swietenioides and Homalium zeylanicum plants were carried out with an intention of finding the type and diversity of phytochemicals present in them. The phytoconstituents in the plant were extracted using ethyl acetate, methanol and water as solvents. The extracts showed positive results for biologically active compounds like alkaloids, flavanoids and phenolic compounds. The quantitative studies indicated that the more components were extracted in highly polar solvent water with high amount of alkaloids (31.00mg/g) in Schrebera swietenioides, and phenolic compounds (20.28mg/g) in Homalium zeylanicum.